2021
DOI: 10.3389/fmicb.2021.767174
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Coral-Associated Bacteria and Symbiodiniaceae in Acropora valida Under Ocean Acidification

Abstract: Ocean acidification is one of many stressors that coral reef ecosystems are currently contending with. Thus, understanding the response of key symbiotic microbes to ocean acidification is of great significance for understanding the adaptation mechanism and development trend of coral holobionts. Here, high-throughput sequencing technology was employed to investigate the coral-associated bacteria and Symbiodiniaceae of the ecologically important coral Acropora valida exposed to different pH gradients. After 30 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 98 publications
(124 reference statements)
0
7
0
Order By: Relevance
“…Corals associated with Cladocopium goreaui (C1) have previously shown elevated photosynthetic efficiency (Cantin et al, 2009;Morgans et al, 2020). It is therefore possible that elevated photosynthesis is a common trait within some taxa from the C1 radiation and may explain the higher photosynthetic efficiency mechanism of C1 to face OA as observed by Ge et al (2021) inAcropora valida . The elevated photosynthetic capacity of A. tenuis in Bouraké, coupled with the dominance of major ITS2 sequence C1, could explain their significantly higher growth rates, as previously observed in A. tenuis juveniles (Cantin et al, 2009;Little et al, 2004).…”
Section: Does Their Symbiodiniaceae Community Raise the Physiology Of...mentioning
confidence: 99%
“…Corals associated with Cladocopium goreaui (C1) have previously shown elevated photosynthetic efficiency (Cantin et al, 2009;Morgans et al, 2020). It is therefore possible that elevated photosynthesis is a common trait within some taxa from the C1 radiation and may explain the higher photosynthetic efficiency mechanism of C1 to face OA as observed by Ge et al (2021) inAcropora valida . The elevated photosynthetic capacity of A. tenuis in Bouraké, coupled with the dominance of major ITS2 sequence C1, could explain their significantly higher growth rates, as previously observed in A. tenuis juveniles (Cantin et al, 2009;Little et al, 2004).…”
Section: Does Their Symbiodiniaceae Community Raise the Physiology Of...mentioning
confidence: 99%
“…Interestingly, however, Bouraké corals exhibited more consistent major ITS2‐type profiles between replicate colonies at low and variable pH than corals from the reference site. Microbiome stability (both for symbionts and/or bacteria) was linked to greater physiological resilience to OA (Ge et al, 2021 ; Grottoli et al, 2018 ; Quigley et al, 2017 , 2019 ; Ros et al, 2021 ), suggesting that consistent major ITS2‐type profiles for Bouraké corals under pH treatments could facilitate their success; however, further work will be needed to verify this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Corals associated with Cladocopium goreaui (C1) have previously shown elevated photosynthetic efficiency with regard to other Symbiodiniaceae species (Cantin et al, 2009;Morgans et al, 2020;Stat, Morris, & Gates, 2008;Wall et al, 2020). It is therefore possible that elevated photosynthesis is a common trait within some taxa from the C1 radiation and may explain the higher photosynthetic efficiency mechanism of C1 to face OA as observed by Ge et al (2021) in Acropora valida. The elevated photosynthetic capacity of A. tenuis in Bouraké, coupled with the dominance of major ITS2 sequence C1, could explain their significantly higher growth rates, as previously observed in A. tenuis juveniles (Cantin et al, 2009;Little et al, 2004).…”
Section: Does Their Symbiodiniaceae Community Raise the Physiology Of...mentioning
confidence: 98%
“…In addition, the circle size of ocean acidification is larger than that of nutrient and most other keywords in Figure 4. However, recent indoor studies demonstrated that Symbiodiniaceae community composition was hardly affected by ocean acidification, suggesting that more field studies on Symbiodiniaceae responses to ocean acidification are required while considering the experimental period and acidification intensity (Ge et al, 2021;Zhou et al, 2021). It is worth mentioning that a field with relatively limited research is not necessarily an unpopular field but can be the latest research field.…”
Section: Co-occurrence Of the Abstract From Coral Or Symbiodiniaceae ...mentioning
confidence: 99%